REGULATORY RELIANCE PATHWAYS: OPPORTUNITIES, CHALLENGES AND FUTURE DIRECTIONS - GNANESHWARI, GURRAM; NAGARAJ, KIRAN; DEWAN, SHAILEE; MANOHARAN, VIGNESH; MURAGUNDI, PRADEEP MANOHAR (International Journal of Applied Pharmaceutics, 2025)
Regulatory reliance allows national agencies to use assessments from trusted regulators instead of repeating the same work. This accelerates approvals, decreases workload, and allows patients to receive safe and effective medications more quickly. Many countries use different forms of reliance procedures, such as work-sharing, mutual recognition, abridged, and verification. These methods are common in regions like the European Union, the United Kingdom, South Africa, and Latin America. Various programs like Project Orbis and The World Health Organization’s (WHO) Collaborative Registration Procedure have reduced review times through collaboration between countries, thereby minimizing resource use and enabling work-sharing. Project Orbis and the Access Consortium have shown the importance of collaborative efforts and their essentiality when dealing with life-threatening diseases. Numerous countries in the Middle East and Asia have used these reliance methods to streamline regulatory processes particularly in public health emergencies. In South African countries, the impact is a 68% reduction in time with regulatory reliance as compared to regular processes. Additionally, the reliance guidelines of WHO initiated the UK’s International Recognition Procedure. During the COVID-19 pandemic regulatory reliance played a pivotal role and facilitated rapid vaccination approvals through international collaboration. Some challenges exist, such as unclear legislation, concerns about independence and legal limitations. Future research should focus on standardizing legislation, modernizing technology like the use of AI-driven evaluations, and improving collaboration as they help to strengthen global coordination to respond to emergencies more promptly. This article explains the reliance pathway and how regulatory decisions from trusted agencies help low-and middle-income countries.